EVALUATING THE EFFECTIVENESS OF USING E-LEARNING IN AL-QALAM UNIVERSITY COLLEGE A CASE STUDY IN THE DEPARTMENT OF BUSINESS ADMINISTRATION - Sarah Mahmoud Ahmed (Scholar Express Journals, 2023)
The research aims to measure the effectiveness of using e-learning in the University AL- Qalam College from the viewpoint of students of the Department of Business Administration, and the research provided a theoretical briefing on some of the contributions made by various researchers and institutions about e-learning, and the questionnaire technique was used to collect the necessary information. To achieve the goals of the research, by asking four axes of questions about (the features of the college experience, the educational process, the success factors of the experiment, it assesses the reality of applying the experiment for the period from 1/3/2020 to the end of June), and a set of results was reached, the most important of them, agreeing on The available e-learning services in the college were good, and the college provided the requirements and factors for the success of implementing e-learning during the stage, and that the experience of applying e-learning despite its positive during the crisis phase, but strengthening it requires the need to pay attention to some of the associated problems, including those related to providing the infrastructure and access To train the administrative and educational staff, there are frequent difficulties for students when entering the website, and continuous interruptions in the Internet line, and concluded the research with a set of proposals
Keywords: e-learning; education effectiveness; measuring the e-learning experience